DEMYSTIFYING HIGHER EDUCATION IN LAW: A STUDENT-TEACHER PERSPECTIVE - Emroj Alam, Hemanshu Rai, Krishna Pal Singh, Kriti Shukla, Monika Shah (Elementary Education Online, 2020)
Purpose: Studying for a master’s degree in law involves many aspects. It’s essential to thoroughly analyze these aspects to understand the gaps in the current higher education system for law in India. This study aims to offer an overview of the educational decisions made for a master’s program, considering the specific goals of the participants. Design/ methodology/ approach: This research serves as a preliminary step towards a larger empirical study aimed at identifying deficiencies in higher education in law, particularly focusing on the perspective of master’s in law students. The viewpoints of teachers will also undergo qualitative and quantitative analysis, making this primarily a doctrinal study supplemented by case studies to illustrate shortcomings in legal higher education. Findings / Probable outcome: The views of students and instructors on a law master’s program should align to improve teaching methods. Discussions on efficacy versus intent, specialized versus generalized learning, practical versus research-focused methods, and traditional versus modern teaching styles strive to develop an innovative framework for advanced legal education. Research limitations/implications: Due to time and resource constraints, the authors did not conduct institution-specific inquiries to determine patterns of legal pedagogy. Therefore, this research is based on the personal experiences of the authors, supplemented by a limited number of questionnaire responses, to analyze current issues in higher education from multiple perspectives. The authors are mindful of potential personal biases that may arise, and as such, the research implications are carefully drawn. Practical implications: The research aims to advance higher legal education in the country. A comprehensive analysis of the student-teacher experience in a master’s classroom will facilitate the development of an effective teaching methodology that enhances student engagement and adds substantial value to the legal academia in the years to come. Originality/value: It sounds like your research is addressing a significant gap in understanding the legal education framework in India, focusing on both student and teacher perspectives. By exploring the challenges faced within higher education, particularly in the legal domain, your aim is to inform effective teaching methods that align with the needs and aspirations of master’s students in India. This approach could potentially lead to improvements in how legal education is delivered and received, ensuring that it meets contemporary standards and prepares students adequately for their professional careers. If you need further insights or suggestions on how to structure your research, feel free to ask!